Studies About Influence Content TikTok On Purchasing Decisions Sudden Young generation - Siti munawaroh; Feri Hardiyanto (Politeknik Siber Cerdika Internasional, 2025)
Phenomenon purchase sudden (impulsive buying) among generation young the more increase along with the development of social media , in particular TikTok , as a very popular visual content platform influential . Various content creative like review products , trends shopping , and video endorsements have the potential form perception and behavior consumer in a way instant . Research This aim For analyze influence content TikTok to decision purchase sudden generation young , with focus on aspects emotional , visualization products , as well as factor social displayed​ in content . Research This use approach quantitative with method survey against 300 respondents active 17–25 year olds​ use TikTok . Data collected through online questionnaire and analyzed use multiple linear regression For know significance variables content TikTok to decision purchase sudden . Research results show that there is influence significant between intensity exposure content TikTok and the decision purchase sudden (p < 0.05). Factor visualization products and encouragement emotional in content own the most dominant contribution . Besides that , social proof like comment positive and number of likes also play a role strengthen decision purchase in a way impulsive . Implications from findings This can become input strategic for perpetrator business in designing campaign effective marketing on the TikTok platform.